ESTUDIO DEL EFECTO DE LA NISINA COMO BIOCONSERVANTE, EN LAS CARACTERÍSTICAS BROMATOLÓGICAS DE PRODUCTOS CÁRNICOS AHUMADOS: POLLO (Gallus gallus domesticus) Y CERDO (Sus scrofa ssp. domestica) - Cervantes García, Oscar Fernando (2023)
The objective of the present study was to provide an alternative to tradicional additives by s analyzing the efficacy of nisin as a biopreservative in smoked meat products, applied in three concentrations (0.5, 1 and 2%), with two types of packaging (polypropylene sleeve and vacuum-sealed) in two types of meat (pork and chicken). A multifactorial AxBxC, design was used, obtaining 12 treatments with 3 replicates, with a total of 36 experimental units. For the significance test, Tukey's multiple range test was used with a margin of error of 5%. Using the statistical software Statgraphics and Minitab, with which the bromatological and microbiological tests were evaluated, giving as best result t11 (nisin 2% + vacuum sealing + pork) and for chicken t8 (nisin 1% + vacuum sealing + chicken) as best treatment, with a determined shelf life of 10 days with the biopreservative in refrigeration at 4 °C with absence of Salmonella, as well as Escherichia Coli, and up to 8.3 x 103 UFC in aerobic mesophiles. Complying with INEN 1338: 2010 and INEN 1347 standards, this product is safe and suitable for consumption.